Digital PID Trainer Based On Arduino For DC Motor Speed Control With Ziegler Nichols Method - Dana Edie Ardana, Dana Edie Ardana; Yulian Zetta Maulana; Gunawan Wibisono (Jurusan Teknik Elektro Universitas Andalas, 2025)
This research aims to design and implement a Proportional Integral Derivative (PID) control system to regulate the speed of a DC motor using the Ziegler Nichols tuning method, focusing on improving the stability and responsiveness of the system for industrial automation applications. The research uses a mathematical model of a DC motor derived from its electrical and mechanical components for simulation and analysis of the system behavior. The PID controller is implemented with the Ziegler Nichols tuning method (open and closed loop) to determine the optimal parameters (Kp, Ki, Kd). The system was tested using Arduino, L298N motor driver, and MATLAB for simulation and analysis. Performance is evaluated based on response characteristics such as rise time, settling time, overshoot, and steady state error. The Ziegler-Nichols method successfully tuned the PID controller with optimal parameters Kp = 11.7, Ki = 1, and Kd = 0.25. Analysis of the system response shows rise time = 0.4866 s, settling time = 2.5829 s, overshoot = 19.6194%, and steady state error = 0.0861%. This PID-controlled system provides fast response and good stability, with significant improvement in reducing steady state error and overshoot compared to systems without controllers or those using trial-and-error tuning. The Ziegler-Nichols tuning method is effective for optimizing PID control in DC motor speed regulation. The proposed system offers a reliable and efficient solution for industrial applications that require precision motor control.